Changes in the explanation of inflation - Ábel, István; Bognár, Gergely; Lóga, Máté; Szabó, István Attila (Public Finance Quarterly, 2024)
Most discussion of inflation in 2021-2022 have focused on product market shocks rather than unemployment indicators. The Phillips curve approach, which provides the traditional theoretical framework, was questioned. In addition to the surge in food and energy prices, many new inflationary factors have come to the fore, such as the disruption in supply chains, as well as fiscal spending and loose monetary policy in the context of the pandemic. These factors do not fit into the traditional approach. In this paper, we review the main literature on the US and European economies to see how the analytical framework represented by the Phillips curve can be adapted to analyse the current situation. Since its inception, the Phillips curve approach has undergone significant changes reflecting changes in the nature of inflation. For example, the unemployment gap was later replaced by the output gap. In the current situation, the output gap has been replaced by arguments in favour of the inclusion of enterprise pricing, marginal cost and the profit rate.